Annotated checklist of the earthworms (Annelida: Clitellata: Oligochaeta) from Hispaniola: a brief review and remarks - Álvarez-Abreu, Oniel; Carrera-Martínez, Roberto (Zootaxa, 2025)
Here, we present an annotated checklist and a brief literature review of earthworms known from the Caribbean island of Hispaniola. A total of 22 species are recorded, with one uncertain species record. Among these species, only 11 are considered native or endemic to the island. Patterns of distribution within Hispaniola are therefore preliminary. Nonetheless, of the 22 recorded species so far, eight are found exclusively in the Dominican Republic and six are restricted to Haiti. The total number of earthworm species on Hispaniola is considerably lower than the known diversity of the other Greater Antilles islands. However, the lower species richness on the island is attributed to limited work and absence of local experts. Systematic surveys will be needed to better understand the basic earthworm diversity of Hispaniola.